Identification Of Infectious Bronchitis Virus Isolates From Malaysia - A. Talip, Balkis (2007)
Infectious bronchitis (IB) is a highly contagious respiratory, urogenital and reproduction disease of chickens and it is distributed worldwide. The disease is caused by infectious bronchitis virus (IBV). IBV is a member of the genus Coronavirus, family Coronaviridae and it has a single-stranded, positive-sense RNA genome of 27.6 kb. It possesses prominent surface spikes and has three major structural proteins; the spike (S) glycoprotein, the small integral membrane (M) glycoprotein and nucleocapsid (N) protein. In the commercial poultry industry, vaccination is used to control the disease. Despite vaccination program the disease continues to occur because IBV can exist in many serotypes. In many incidences, the existing vaccines are not able to provide full protection to the chickens against infectious bronchitis disease. The immune response stimulated to one serotype does not offer cross protection to another serotype. Moreover, the avian coronavirus capable of mutating and many IBV variants has been reported in many countries. Thus, it is crucial to develop a fast, sensitive and specific diagnostic technique to diagnose and identify the causative agent in order to control the disease spread. In recent years the reverse transcriptase-polymerase chain reaction (RT-PCR), reverse transcriptase-polymerase chain reaction-restriction fragment length polymorphism (RT-PCR-RFLP), cloning and genes sequencing had been used increasingly to detect and analyses IBV isolates. The objectives of these studies were to compare and optimize reverse transcriptase-polymerase chain reaction (RT-PCR) to diagnose IBV, to differentiate the Mass strain, and to characterize variant IBV isolated from this study. In this study, one-step and two-step RT-PCR techniques were used to amplify the conserved gene region of IBV by using universal and designed primers. This study was conducted on IBV isolates from year 1991 until 2003. In differentiation studies, isolates were group into serotype using reverse transcriptase-polymerase chain reaction (RT-PCR). Isolates recognized to be non Mass was further amplified their hypervariable region of S gene by using RT-PCR followed by RFLP technique to screen for nephropathogenic strain. Out of 31 IBV isolates, nine Mass strain were found. Following RT-PCR-RFLP, only one isolate showed different fragment pattern compared to nephropathogenic origin (MH5365/95). This particular isolates designated as V9/03 was neither Mass nor non-nephropathogenic serotype. The S1 region of V9/03 was further cloned, sequenced and its nucleotide and amino acid were compared to nephropathogenic MH5365/95 and Mass derivatives as well other references strains obtained from Gene bank. The V9/03 showed sequence homology to Taiwan (AY606321) and Korean (AY257060) strain with 82.5% and 81.6% identities respectively. The V9/03 has lower sequences homology (less than 80%) with nephropathogenic (MH5365/95) and Mass derivatives. The phylogenetic studies indicate that the strain V9/03 could be a local variant IBV which is different from local nephropathogenic MH5365/95 and vaccine strain. This study showed that variant IBV is circulating in the field as result of mutation of IBV due to the prolonged use of live virus vaccines and the immunological pressure of the virus to keep on survival in immune birds.